Budgeting Gamesmanship in Real Estate and Construction: A Study of Msme’s - Ida Farida; Falikhatun Falikhatun (Universitas Swadaya Gunung Jati, 2023)
AbstractThis study aims to seek how the process of budget preparation, implementation, and execution in the MSMEs Real Estate and Construction sector. The research focuses on the possibility of Gamesmanship in the budgeting process. This research is a case study with descriptive analysis method. Data was collected through in-depth interviews with several MSMEs business actors who contribute to the enterprise budgeting process. Budget gaming may happen because of a conflict of interest by a divisional or individual. This research picturing the budgeting process in real estate and construction MSME’s and also reveals that the variables of the level of budget difficulty and the level of participation support the practice of budget gaming. The implementation of feedback and evaluation of the budget is going quite well by top-level management. Either contributes to the literatures, this research also trying to give advice to government as regulator that the importance of the budget for the sustainability of MSMEs should be a concern, especially for micro-enterprises to level up. And hopefully, training and good budgeting practices can be echoed more often to MSMEs business actors in the real-estate and construction sector.Keywords: Budgeting; Construction; Gamesmanship; Real estate.AbstrakPenelitian ini bertujuan mengungkap bagaimana proses penyusunan, pelaksanaan, dan evaluasi anggaran pada UMKM di sektor Real Estate dan Konstruksi. Penelitian ini berfokus pada kemungkinan Gamesmanship dalam proses penganggaran. Penelitian ini merupakan studi kasus dengan metode analisis deskriptif. Data dikumpulkan melalui wawancara mendalam dengan beberapa pelaku usaha UMKM yang berkontribusi dalam proses penganggaran perusahaan. Diketahui bahwa terdapat praktik permainan anggaran dalam proses penganggaran. Permainan anggaran dapat terjadi karena konflik kepentingan oleh divisi atau individu. Penelitian ini memberi gambaran proses penganggaran pada UMKM sektor real estate dan konstruksi, dan bahwa variabel tingkat kesulitan anggaran dan tingkat partisipasi mendukung praktik permainan anggaran. Implementasi umpan balik dan evaluasi anggaran berjalan cukup baik oleh manajemen tingkat atas. Selain berkontribusi pada literatur terkait, penelitian ini mencoba memberikan saran kepada pemerintah sebagai regulator bahwa pentingnya anggaran bagi keberlangsungan UMKM harus menjadi perhatian, khususnya bagi usaha mikro yang menjadi perhatian besar akhir-akhir ini oleh pemerintah untuk dikembangkan sehingga naik level. Pada akhirnya, peneliti berharap praktik pelatihan dan penganggaran yang baik dapat lebih sering digaungkan kepada pelaku usaha UMKM di sektor real estate dan konstruksi.Kata Kunci: Anggaran; Gamesmanship; Konstruksi; Real estate.